Pengaruh Model Pembelajaran Cooperative Tipe Jigsaw Oleh Guru PAK terhadap Motivasi Belajar Siswa Kelas VIII SMP N 2 Sipoholon Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Ester Magdalena Nababan; Elisamark Sitopu; Ronny Simatupang; Dorlan Naibaho; Sabar Rudi Sitompul (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The purpose of this study was to determine how much the positive and significant effect of the Jigsaw Type Cooperative Learning Model by PAK Teachers on the Learning Motivation of Students of SMP Negeri 2 Sipoholon, North Tapanuli Regency in the 2023/2024 Learning Year. The research method used is descriptive quantitative method with inferential statistical approach. The population was all VIII grade students at SMP N 2 Sipoholon, Learning Year 2023/2024 as many as 120 people and a sample of 44 people was determined using probability sampling technique with a random type (simple random sampling). Data was collected using a positive closed questionnaire of 42 items, namely 22 items for variable X and 20 items for variable Y. The results of data analysis show that there is a positive and significant effect of the Jigsaw Type Cooperative Learning Model by PAK Teachers on the Learning Motivation of VIII grade students of SMP Negeri 2 Sipoholon, North Tapanuli Regency, Learning Year 2023/2024: 1) Test of analysis requirements: a) positive relationship test obtained rxy value = 0.488 > rtable (=0.05, n=44) = 0.297. b) Significant relationship test obtained tcount = 3.626 > ttable (=0.05, dk=n-2=42)=2.021). 2) Effect test: a) Regression equation test, obtained regression equation. b) Regression determination coefficient test (r2) = 23.8%. 3) Hypothesis testing using the F test obtained Fhitung> Ftabel = (=0.05, dk numerator k = 20, dk denominator = n-2 = 44-2 = 42) which is 13.18 > 1.51. Thus Ha is accepted and H0 is rejected. It can be concluded that with the Jigsaw Type Cooperative Learning Model by the PAK Teacher which can maximally increase student learning motivation at SMP Negeri 2 Sipoholon, North Tapanuli Regency, Learning Year 2023/2024.